Experimental Investigations on the Performance of a Single Slope Solar Still Coupled with Shallow Solar Pond under Malaysian Conditions - Z. A., Kamarulbaharin; M.A, Safie; A.M, Azmi; B.S.B, Singh (International Journal of Engineering and Technology, 2018)
Water is important to life. Deprived of water, humans can only survive for a few days. Oceans offer unlimited supply of water but it could not be ingested by humans on account of its high salt content. Desalination using fossil fuels as an energy source is expensive and may harm the environment. On the other hand, solar energy which is renewable and environmentally friendly can be used as a cheaper alternative. This paper aims to investigate the performance of a single slope solar still coupled with shallow solar pond of different design parameters under Malaysian conditions. Results showed that the performance of stills coupled with shallow solar pond is better than the ones without. The active still with the steepest condenser tilt angle (20o) yielded the highest productivity of 119 ml of water as compared to the 3o tilt angle passive still (8.5 ml).Â Â